Delivery of therapeutic RNA-cleaving oligodeoxyribonucleotides (deoxyribozymes): from cell culture studies to clinical trials. (2nd September 2017) - Fokina, Alesya A.; Chelobanov, Boris P.; Fujii, Masayuki; Stetsenko, Dmitry A.
ABSTRACT: Introduction . Development of efficient in vivo delivery systems remains a major challenge en route to clinical application of antisense technology, including RNA-cleaving molecules such as deoxyribozymes (DNAzymes). The mechanisms of oligonucleotide uptake and trafficking are clearly dependent on cell type and the type of oligonucleotide analogue. It appears likely that each particular disease target would pose its own specific requirements for a delivery method. Areas covered . In this review we will discuss the available options for DNAzyme delivery in vitro and in vivo, outline various exogenous and endogenous strategies that have been, or are still being, developed and ascertain their applicability with emphasis on those methods that are currently being used in clinical trials. Expert opinion . The available information suggests that a practical system for in vivo delivery has to be biodegradable, as to minimize concerns over long-term toxicity, it should not accumulate in the organism. Extracellular vesicles may offer the most organic way for drug delivery especially as they can be fused with artificial liposomes to produce hybrid nanoparticles. Chemical modification of DNAzymes holds great potential to apply oligonucleotide analogs that would not only be resistant to nuclease digestion, but also able to penetrate cells without external delivery agents.